Particulated microalgae composite (PMC) as substitute for live microalgae in culture of juvenile Manila clam Ruditapes philippinarum (A. Adams and Reeve, 1850): A feasibility analysis - Liang, Jian; Bi, Xiangdong; Dai, Wei; Deng, Yuewen (Indian Journal of Fisheries, 2021)
To evaluate the feasibility of particulated microalgae composite (PMC) as live microalgae substitute in artificial breeding of Manila clam Ruditapes philippinarum, effects of replacing Dicrateria inornata with partial or total PMC on the growth, digestive enzyme activities, nutritional ingredient composition and microbial composition in faeces of juvenile clams were investigated. The results showed that 50 and 100% PMC replacement did not affect the mean shell length, mean body weight and survival rate of juvenile clams (p>0.05). Juvenile clams fed with 100% PMC replacement had higher lipase and pepsin activities than those fed with 100% D. inornata (p<0.05), while 50% PMC replacement only increased lipase activity (p<0.05). Essential amino acid (EAA) and polyunsaturated fatty acid (PUFA) contents exhibited no obvious differences between clams fed with and without PMC replacement (p>0.05). Significant increase in delicious amino acid contents (p<0.05) was observed with 100% PMC replacement. PMC replacement did not affect the diversity of dominant phyla in faeces, but the abundance of each dominant phylum. Similar relative abundance of faecal bacteria was observed when D. inornata was replaced with 50 and 100% PMC. PMC appeared to be a potential substitute for microalgae in artificial Manila clam breeding. Keywords: Dicrateria inornata, Microalgae substitute, Particulated microalgae composite, Ruditapes philippinarum